Evaluating the impact of the discussion method on enhancing high school students' foreign language communicative skills - Zhanar Bakirova (Reviews of Modern Science, 2024)
This study focuses on evaluating the effectiveness of the discussion method in enhancing the foreign language communicative competence of high school students. The research involved defining the primary goals and objectives and developing a methodology for facilitating discussions in a foreign language with high school students. To assess the method's effectiveness, an experiment was conducted with high school students who were divided into control and experimental groups.